UPLC-TOF/MS-based metabolomics reveals the chemical changes and in vitro biological effects in fermentation of white ginseng by four probiotics - Chen, Yincui; Wang, Yunsheng; Zhu, Anqin; Zhang, Liqin; Zhang, Xiang; Zhang, Jin; Zhang, Chuanbo (Frontiers in Microbiology, 2022)
Microbial fermentation is a useful method for improving the biological activity of biomaterials. Herein, we reveal the effects of solid-state fermentation on total flavonoid and phenol content, as well as antioxidants (the reducing antioxidant power, ABTS radical scavenging activity, DPPH radical scavenging activity), α-amylase inhibitory activities, and α-glucosidase inhibitory activities on white ginseng (WG). Metabolite differences between non-fermented and different strains of fermented WG were investigated by LC-MS/MS. Results showed that that the total flavonoid content, ferric reducing antioxidant power, scavenging activities of DPPH radical and ABTS, α-amylase inhibitory activities, and α-glucosidase inhibitory activities of WG were considerably enhanced after processing by SSF in all strains. The total phenol content was increased by Eurotium cristatum and Bacillus licheniformis fermentation, but decreased by Lactobacillus plantarum, Saccharomyces cerevisiae, and multi strain fermentation. Additionally, E. cristatum exhibited improved biotransformation activity on WG samples compared to other strains. Significant differentially expressed metabolites were mainly annotated as prenol lipids, carboxylic acids, and derivatives, flavonoids, polyphenols, coumarins, and derivatives. Correlation analysis further showed that changes in these metabolites were closely related to antioxidant and hypoglycemic effects. Here, we show that fermentation by different microorganisms has distinct effects on the biological activities and metabolite composition of WG. The above results indicate SSF with microorganisms as an important novel strategy to promote components and bioactivities of WG.